Rola wartości w psychospołecznym radzeniu sobie ze stresem u studentów - Wośko, Patrycja (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
This article presents an assessment of key academic values that enhance students’ academic effectiveness and coping with stress resulting from functioning in the academic community. It provides valuable knowledge that allows for a better understanding of aspects contributing to students’ full engagement in learning and academic activities. The main objective of the study was to identify the relationships between socio-organizational factors in the academic environment and the coping strategies used by students to deal with stress. The study group consisted of 1210 students from the John Paul II Catholic University of Lublin. The research was conducted using a tool analyzing the importance of key areas of university functioning – the Assessment of Socio-Organizational Factors in the Academic Environment (a proprietary tool), and the Mini-COPE, which examines stress coping strategies. A supportive academic environment contributes to students’ active coping with stress and seeking support, while reducing the tendency to feel helpless. Interpersonal relationships, autonomy, and task clarity are key protective factors in stressful academic situations. The conducted research provides guidance on how to identify students’ needs and expectations and how to support them in their psychosocial functioning by developing effective methods of coping with stress.